The "Thunen-Archiv" - G., E. F. (Quarterly Journal of Economics, 1904)
The “Thünen-Archiv” Get access The Quarterly Journal of Economics, Volume 19, Issue 1, November 1904, Pages 149–151, https://doi.org/10.2307/1884868 Published: 01 November 1904